(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2018)
L’articolo si interroga sulla relazione fra la tecnologia digitale e l’emergere di un rinnovato interesse per il dettato testuale trasmesso dalle fonti primarie e il conseguente aumento delle edizioni diplomatiche. Dall’analisi della testualità multiforme del periodo medioevale, si passa alla rassegna delle motivazioni sociali, economiche e culturali che hanno portato all’elaborazione dell’idea del Testo Unico, messo in discussione dall’avvento del digitale. The text is dead: long life to the texts. Textual pluralism and digital editions This article questions the relationship between digital technology and the emergence of a renewed interest in the text as transmitted by documents and the consequent increase in the production of diplomatic editions. From an analysis of the multifaceted textuality of the medieval period, the article moves on to review the social, economic and cultural motivations that led to the elaboration of the idea of the Only Text, an idea that is now challenged by the advent of the digital.